Active aeroelastic wing application on a forward swept wing configuration. Issue 1 (1st January 2019) - Xue, Rongrong; Ye, Zhengyin; Ye, Kun
Abstract : Active aeroelastic wing is introduced to benefit the forward swept wing (FSW) aeroelastic performance owing to the FSW's elaborate aeroelastic problem.In this research, a computational aeroelastic (CAE) code was developed to conduct aeroelastic simulations, which presents challenges of data interpolation and flow capturing since torsional deformations instead of bending dominate in FSW deformation and separations on FSW occur earlier due to the boundary layer accumulation. Two simulations are conducted to verify the adaptability and accuracy of CAE method on FSW. CAE simulations are conducted on a straight FSW with control surfaces in two phases. The results from first phase obtained at Mach 0.8 demonstrate that negative deflection of LE and positive deflection of TE can effectively depress the torsion angle and root-bending moment at identical lift. Deflections of LE 0°, TE +20° can reduce LE and TE wingtip displacement by 36.53% and 39.87%, respectively, resulting in 78.97% decline of torsion angle. The second-phase calculations, conducted at Mach 0.9 at different dynamic pressures, illustrate depression of FSW torsion and deformation by LE and TE downward deflection. The LE and TE control effectiveness is always beyond 1 and the control power of the FSW increases with increasing dynamic pressure.